Why do firms hedge? a revisit for an emerging market perspective - Adilah A. Wahab,; Rozaimah Zainudin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explores the determinants of hedging practices, focusing on foreign exchange exposure within 250 listed Malaysian firms. Aligned with the theory of underinvestment costs, a positive correlation between foreign exchange exposure and hedging is established. Firms with higher exposure display an increased propensity for hedging contracts, and the COVID-19 pandemic significantly impacts these practices. Quantile regression analysis reveals that heightened foreign exchange exposure induces Malaysian firms to intensify hedging, particularly in lower and middle distribution percentiles. Additionally, the study highlights the impact of growth opportunities on the intricate relationship between foreign exchange exposure and hedging practices. Implications include strategic consideration of foreign cash flow-based exposure in hedging decisions, recognizing hedging as pivotal during crises, and acknowledging the motivating role of growth opportunities in fostering increased hedging within a corporate framework.